Challenges and opportunities in decarbonizing the U.S. energy system. (November 2022) - Arent, Douglas J.; Green, Peter; Abdullah, Zia; Barnes, Teresa; Bauer, Sage; Bernstein, Andrey; Berry, Derek; Berry, Joe; Burrell, Tony; Carpenter, Birdie; Cochran, Jaquelin; Cortright, Randy; et al.
Abstract: The United States has pledged to develop a 100% carbon-free electric power system by 2035 and a net-zero-emissions economy by 2050. While important advancements have been made in the scale, performance, and economics of clean energy technologies, meeting the nation's ambitious goals will not only require their deployment at scale, but also additional innovation and effective integration of different solutions. Technological developments across the broad suite of low-carbon energy solutions are advancing rapidly, with ongoing innovations in renewable electricity generation, industrial processes, and energy-saving technologies and services, including LED lighting, induction heating, electric vehicles, energy storage solutions, and mobility as a service, plus smart devices, controls, and more efficient and smart buildings. Combining renewable electricity with biotic and abiotic pathways to produce chemicals, fuels, and materials promises to deliver new solutions. Grid-interactive buildings and communities, integrating transportation infrastructure and vehicles, are likely to be significant components of any zero-carbon energy strategy. Low-carbon industrial manufacturing will also make strong contributions to a net-zero economy. While the technical prospects appear promising, variations in the state of infrastructure, jurisdictional and social equity, pollution, economic and socio-cultural constraints, energy resource availability, and supply chain dynamics found in different locations present a range of challenges and demand customized solutions. This paper provides a critical review and offers new insights into the technical, infrastructure, analytic, political, and economic challenges faced in translating the nation's ambitious net-zero-emissions goals into feasible and reliable implementation action plans. Highlights: This manuscript brings together multiple experts view on the State of technologies, System level solutions, economics and scaling, for the United States to achieve bold decarbonization goals by 2050. Key insights are offered on power system decarbonization, the role of hydrogen, storage, transportation, integrated energy systems, and material utilization and circularity. Technologies, particularly wind and solar, are increasingly cost-effective, yet challenges remain regarding integration, social and political economy issues, and energy and environmental justice. While the technical and economic factors are increasingly favorable, the US faces a number of non-technical challenges to rapidly scale clean energy technologies in order to achieve its ambitious goals.